The Effectiveness Of Electronic Word Of Mouth (E-Wom) In Student’s Decision To Choose A Flight Attendant School - Kurniawan, Andi (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
E-WOM is a communication tool in the field of marketing, especially on social media which is able to increase buying interest in the products offered. The power of electronic word of mouth (e-WOM) has begun to be realized by flight attendant schools to introduce their school through social media. This can be seen from the proliferation of flight attendant schools that offer their products on social media using e-WOM to provide good advice on product services. The purpose of this research is to provide knowledge development and insight related to the effectiveness of Electronic Word of Mouth (e-WOM) in increasing students’ interest in making decisions about choosing a flight attendant school. The type of research used is descriptive qualitative with literature study method. The results of this study that Electronic Word of Mouth (e-WOM) can increase one’s interest in a school service on social media. These results are supported by several studies that show e-WOM can improve students’ decisions to choose a flight attendant school.